Relationship between Appropriate Antibiotics Used based on 2019 ATS/IDSA Guideline and Clinical Improvement in Inpatient Community Pneumonia Patients - Maju, Mensiana Ayu; Setiawan, Christianus Heru (Universitas Ahmad Dahlan, 2023)
Community pneumonia is a serious infection obtained from the community environment, and one of the causes is bacteria. This infection causes lung inflammation and leads to death if not treated properly. The appropriate of empirical antibiotics can increase the success of therapy and prevent the emergence of bacterial resistance to various kinds of antibiotics. This study aims to assess the appropriateness of empiric antibiotic selection in community pneumonia using the 2019 ATS/IDSA antibiotic guideline and analyze its relationship with the patient's clinical response. This study is a retrospective cohort design type. Medical record data obtained, namely antibiotics and clinical response, were analyzed using the Mann-Whitney statistical test. There were differences in the average clinical improvement, including body temperature, heart rate, and respiratory rate, in the group of community pneumonia patients who used empiric antibiotics according to the guideline and those who did not follow the guidelines 2019 (P<0.05). According to the result, empiric antibiotics based on the 2019 ATS/IDSA guideline can increase therapy outcomes in inpatient community pneumonia patients.